Pelatihan dan Pendampingan Teknik Budidaya Ikan Dalam Ember (BUDIKDAMBER) di Desa Sumberagung Jombang - Kartika Wulandari; Abu Na'im; Elly Septiana Dwi Kusuma; Ibnu Rozak; Komalasari Komalasari (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Sumberagung Megaluh Jombang Village, where the majority of the population work as farmers. The technique of cultivating catfish in buckets is still classified as a new innovation and is relatively unknown to the public. This community service activity aims to provide information on cultivation using the technique of cultivating fish in buckets, which is also called BUDIKDAMBER. This technique has advantages in land use for cultivating catfish and pokcoy vegetables using buckets and does not require large areas of land. This cultivation uses quite economical media such as used buckets, used plastic cups, a little water, and is easy to move. The activity will be carried out in October 2022. Starting with the survey stage, discussions with the community, procurement of tools and materials, training, to evaluation and monitoring of cultivation results. Conducting the Budikdamber training with PKK women in groups, the division of 30 members was divided into 5 groups so that each group had 6 PKK members, each group received 40 catfish seeds and 8 plastic cups of pakcoy horticultural vegetables. The results of the activity evaluation questionnaire showed that 27.79% of partners